2004
DOI: 10.1590/s0104-42302004000100034
|View full text |Cite
|
Sign up to set email alerts
|

O efeito das bebidas alcoólicas pode ser afetado pela combinação com bebidas energéticas? Um estudo com usuários

Abstract: 48FERREIRA SE ET AL.RESUMO -OBJETIVO. Avaliar em uma amostra de critério, o padrão de uso de bebidas energéticas, isoladamente e em associação com bebidas alcoólicas.MÉTODOS. Cento e trinta e seis voluntários (idade 24 ± 6 anos) que relataram ao menos um uso anterior de bebidas energéticas foram submetidos a uma entrevista padronizada sobre hábitos de consumo de bebidas energéticas e alcoólicas.RESULTADOS. A maioria da amostra relatou usar bebidas energéticas tanto isoladamente (79%) como em combinação com beb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
0
11
0
4
Order By: Relevance
“…O uso de bebidas energéticas está diretamente relacionado ao consumo de álcool. Ferreira, já em 2004, apontava para a rápida popularização da ingestão de bebidas alcoólicas, principalmente destiladas, em combinação com bebidas energéticas 35 .…”
Section: Discussionunclassified
“…O uso de bebidas energéticas está diretamente relacionado ao consumo de álcool. Ferreira, já em 2004, apontava para a rápida popularização da ingestão de bebidas alcoólicas, principalmente destiladas, em combinação com bebidas energéticas 35 .…”
Section: Discussionunclassified
“…The combined administration of ethanol and taurine is popularly used as a recreational drink to increase sensations of pleasure and to reduce the intensity of some depressant effects of ethanol on the nervous system [ 15 ]. In addition, studies have shown that the O 2 max does not significantly change with the ingestion of ethanol when it is or is not combined with energy drink intake [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ingestion of energy drinks containing taurine in combination with alcoholic beverages has been used to reduce the depressant effects of ethanol [ 15 ], although some research did not report these results [ 16 ]. Oxygen consumption during exercise has been evaluated after ingestion of mixed energy drinks and alcohol [ 17 ], but the short time of the intake prior to the exercise (<1 hour) is not sufficient to analyze the acute effect of the influence of taurine, since the peak plasma concentration of this amino acid occurs at approximately two hours after intake [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol intake commonly occurs together with energy drinks, which contain an amino acid called taurine (TA), which objective is to reduce the symptons of depression [ 6 ]. Due to the different components contained in energy drinks, it is difficult to affirm the effects of each substance interacting with ethanol.…”
Section: Introductionmentioning
confidence: 99%